2020
DOI: 10.4236/ampc.2020.102004
|View full text |Cite
|
Sign up to set email alerts
|

ArcGIS<sup>TM</sup> and Principal Component Analysis of Probe Data to Micro-Map Minerals in Round Top Rare Earth Deposit

Abstract: Rare earth elements (REEs), especially heavy rare earth elements (HREEs), are in demand for their current and emerging applications in advanced technologies. Here we perform computer-driven micro-mapping at the millimeter scale of the minerals that comprise Round Top Mountain, in west Texas, USA. This large rhyolite deposit is enriched in HREEs and such other critical elements as Li, Be, and U. Electron probe microanalysis of 2 × 2 mm areas of thin sections of the rhyolite produced individual maps of 16 elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In an earlier work [9] we showed that overlaying the X-ray element maps in ArcGIS™ revealed element-mineral correlations to produce mineralogical maps. In this paper we described the use of those detailed maps to study the placement of minor and accessory minerals, relative to one another in order to understand mineral relationships at the micrometer-to-millimeter scale.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In an earlier work [9] we showed that overlaying the X-ray element maps in ArcGIS™ revealed element-mineral correlations to produce mineralogical maps. In this paper we described the use of those detailed maps to study the placement of minor and accessory minerals, relative to one another in order to understand mineral relationships at the micrometer-to-millimeter scale.…”
Section: Discussionmentioning
confidence: 98%
“…This research is an extension of previous work on the Round Top Mountain deposit in which multivariate statistical analysis (principal component analysis) converted electron microprobe elemental maps [8] into mineral maps [9]. In the current paper, those mineral maps are further analyzed spatially through proximity and cluster analyses using tools in the ArcGIS™ software system.…”
Section: Approach and Purposementioning
confidence: 96%
“…Analytical techniques for RS are grouped into data-driven and knowledge-based techniques [15]. Several techniques, such as band ratios [16,17], band ratio matrix transformation (BRMT) [18], spectral angle mappers (SAM) [19,20], decorrelation stretching (DS) [17,21], principal components analysis (PCA) [17,22,23], directed principal component analysis (DPCA) [24], feature-oriented principal components selection (FPCS) also known as Crosta technique [25][26][27], spatially weighted PCA [28,29], directed PCA [30,31], and other variants of PCA [32], have been reported for mapping different lithological [33] and environmental [34] features. Recently, Support Vector Machine (SVM), PCA, and independent component analysis (ICA) have been used to map gold-bearing granite-greenstone rocks using AVIRIS-NG hyperspectral and ASTER data [35].…”
Section: Introductionmentioning
confidence: 99%